Experimental evaluation of the effect of braking torque on bogie dynamics. (5th November 2007) - Dhanasekar, M.; Cole, C.; Handoko, Y.
This paper reports a full-scale laboratory test carried out for the evaluation of the effect of braking torque on bogie dynamics. Precision instruments have been used as the limited length of the track restricted the operating speed to less than 4m/s. It is shown that by judiciously controlling the brake pressure and its application time, the skid of the braked wheelset could be achieved. The instrumented bogie is shown to possess excellent potential for being used as an onboard system for monitoring the dynamics of cash trains during brake application without the need for a wayside magnetic encoder system.